OS X Mountain Lion server for dummies - Rizzo, John (--For dummies., 2012)
Create a Mac network in your home or office There's no doubt about it: Macs, iPhones, and iPads have invaded the workplace. But, you don't need an IT department to administer a Mac network in your home or business. This friendly guide explains everything you need to know to set one up yourself using OS X Mountain Lion Server. First, you'll find an easy, quick-start way to implement OS X Mountain Lion on a Mac Mini. From there, you'll learn how to set up DNS, iCal Server, Podcast Producer, Wiki Server, file sharing, mail services, and more. This book helps you set up profile support for your i.